Design metalloxidischer Nanopartikel mittels kontinuierlicher hydrothermaler Synthese. Issue 4 (26th January 2018) - Türk, Michael
Abstract: Continuous hydrothermal synthesis using near‐ and supercritical water has been recognized as a green process for the production of metal oxide nanoparticles. This process exploits the strong variations in the thermophysical properties of water around its critical point and is based on the mixing of a cold aqueous metal salt solution with hot compressed water. First, this contribution will give an introduction into the basic principles of the process. Based on this, the current state is described and selected experimental and modeling results are presented and discussed. The main conclusions and further perspectives are summarized.